Association between creatinine clearance and mortality in Chinese patients with osteoporotic fractures: a retrospective cohort study - Su, Ming; Zhou, Peng; Xu, Min-zhe; Gong, Ya-qin; Jin, Jian; Hu, Wen-bin; Lu, Ke; Li, Chong; Yin, Yi (Frontiers in Medicine, 2025)
BackgroundCreatinine clearance (CCR) is a vital biomarker for evaluating renal function, indicating the efficiency of the kidneys in filtering blood waste. However, the link between CCR and mortality in hospitalized patients with osteoporotic fractures (OPFs) remains unclear. The increasing prevalence of OPFs in elderly populations, coupled with known complications of renal dysfunction, underscores the critical importance of understanding this relationship. This study aimed to investigate the association between CCR levels and mortality in a cohort of hospitalized patients with OPFs, with the goal of establishing evidence-based guidelines for risk stratification and management strategies.MethodsA retrospective cohort study analyzed data from 3,177 patients hospitalized with OPFs between 6 December 2018 and 31 December 2023. A multivariate Cox regression analysis was used to evaluate the relationship between CCR and mortality while adjusting for potential confounding variables, including laboratory parameters, clinical characteristics, and lifestyle factors. Subgroup analyses, smoothed curve fitting with threshold analyses, Kaplan–Meier curves, and sensitivity analyses were performed.ResultsA linear correlation between CCR and mortality was observed, with each 1-point increment in CCR correlating with a 2% reduction in mortality risk (hazard ratio (HR) = 0.98; 95% confidence interval (CI): 0.97, 0.98; p < 0.01). Patients were categorized into three groups based on CCR: Group 1 (CCR ≤ 80 mL/min), Group 2 (80 < CCR ≤ 120 mL/min), and Group 3 (CCR > 120 mL/min). Group 2 exhibited a 51% lower hazard of mortality than Group 1 (HR = 0.49, 95% CI: 0.34, 0.71; p < 0.01), while Group 3 showed an 87% reduction in mortality risk (HR = 0.13, 95% CI: 0.05, 0.36; p < 0.01). Subgroup analyses confirmed the robustness of these findings even after adjusting for other covariates. Linear association was detected using smoothed curve fitting and threshold analysis. The Kaplan–Meier survival curves revealed a negative relationship between CCR levels and the cumulative mortality hazard. Sensitivity analyses demonstrated a stable direct association between CCR and the cumulative mortality hazard.ConclusionThis study demonstrated a significant association between CCR and mortality among hospitalized patients with OPFs, validating CCR as a valuable prognostic marker for assessing mortality risk.